Adjustment-style: from H. G. Wells to Ali Smith and the metamodern novel . Issue 6 (3rd June 2021) - Masters, Ben
ABSTRACT: The Wells-James debate about the function of the novel has influenced decades of formalist and humanist criticism that has elevated Henry James as the quintessential ethical stylist and struggled to come to terms with H.G. Wells's literary artistry. This article reevaluates Wells's early fiction as the work of a self-conscious stylist who developed a politically and ethically motivated aesthetic that it calls 'adjustment-style.' It then highlights Wells's significance for a modernist-influenced strand of twenty-first-century writing from which critical common sense has excluded him as forebear, by reading the confluences between his work and that of Ali Smith. In doing so it aims to add nuances to the emergent conceptualisation of the metamodern novel which, it argues, is characterised by its own forms of adjustment-style. It contends that a close reading of Smith's metamodern style makes Wells more visible in our view of the contemporary novel; just as placing Smith in a continuum with Wells illuminates her own distinctive style and challenges many of the familiar novelistic binaries that have been extrapolated from the Wells-James debate.